2001
DOI: 10.2169/internalmedicine.40.1050
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Wegener's Granulomatosis with Initial Clinical Presentations of Henoch-Schoenlein Purpura.

Abstract: The initial presentation of a patient with Wegener's granulomatosis was indistinguishable from that of HenochSchonlein purpura. The patient presented with skin purpura and pulmonary hemorrhage followed by purpura in the colon. The diagnosis of this patient at that time was Henoch-Schonlein purpura. With time, massive lesions in the sinus and those with cavities in the lung became apparent, and a specimen obtained from the sinus massive lesion was disclosed to be granulomatous inflammation. Retrospectively, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…3,13 Miata and colleagues reported a GPA young case (19-years-old) who initially diagnosed as HSP. 5 Four years later, the appearance of polyarthralgia which followed by skin purpura and melena suggested recurrence of IgA vasculitis; however, with time, massive lesion in the sinuses and cavities in the lung which appeared in the age of 28 her sinus biopsy revealed that she suffered from GPA. In other case report, a case of IgA vasculitis followed by WG was described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,13 Miata and colleagues reported a GPA young case (19-years-old) who initially diagnosed as HSP. 5 Four years later, the appearance of polyarthralgia which followed by skin purpura and melena suggested recurrence of IgA vasculitis; however, with time, massive lesion in the sinuses and cavities in the lung which appeared in the age of 28 her sinus biopsy revealed that she suffered from GPA. In other case report, a case of IgA vasculitis followed by WG was described.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 IgA vasculitis (Henoch-Schonlein purpura) is one of the most common pediatric-onset vasculitides which characterized by non-thrombocytopenic palpable purpura, arthritis, bowel angina, and glomerulonephritis. [3][4][5] On the other hand, Granulomatosis with polyangiitis (GPA) or Wegener's Granulomatosis (WG) is a potentially life-threatening vasculitis commonly affecting upper and lower respiratory tract, kidneys, and peripheral and central nervous system. [6][7][8] Although it is more frequent in adult, few cases in children have been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HSP is not associated with ANCA, a clinical overlap with AAV has been described. 11,12 Ronda et al 13 detected IgA ANCA in sera from 11 (79%) of 14 adult patients with HSP, from 1 (3%) of 30 patients with IgA nephropathy, from 1 (2.5%) of 40 patients with IgG ANCA, and in none of 60 healthy blood donors. In 3 patients with HSP, IgG ANCA and IgA ANCA occurred concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous involvement of skin and gastrointestinal symptoms can result in an incorrect diagnosis of Henoch-Schönlein purpura. 66 It is generally thought that if the skin is not involved, or only mildly so, there is a better prognosis for the patient. 62,67 The skin lesions tend to parallel other organs' disease activity and often portend impending renal involvement.…”
Section: Wg -Cutaneous Involvementmentioning
confidence: 99%